Regions of interest on Ganymede's and Callisto's surfaces as potential targets for ESA's JUICE mission. (15th November 2021) - Stephan, K.; Roatsch, T.; Tosi, F.; Matz, K.-D.; Kersten, E.; Wagner, R.; Molyneux, P.; Palumbo, P.; Poulet, F.; Hussmann, H.; Barabash, S.; Bruzzone, L.; et al.
Abstract: The JUpiter Icy moons Explorer (JUICE) will investigate Ganymede's and Callisto's surfaces and subsurfaces from orbit to explore the geologic processes that have shaped and altered their surfaces by impact, tectonics, possible cryovolcanism, space weathering due to micrometeorites, radiation and charged particles as well as explore the structure and properties of the icy crust and liquid shell (Grasset et al., 2013). The best possible synergy of the JUICE instruments is required to answer the major science objective of this mission and to fully exploit the potential of the JUICE mission. Therefore, the JUICE team is aiming to define high priority targets on both Ganymede's and Callisto's surfaces to support the coordination of the planning activities by the individual instrument teams. Based on the science objectives of the JUICE mission and the most recent knowledge of Ganymede's and Callisto's geologic evolution we propose a collection of Regions of Interest (RoIs), which characterize surface features and terrain types representing important traces of geologic processes, from past and/or present cryovolcanic and tectonic activity to space weathering processes, which are crucial to understand the geologic evolution of Ganymede and Callisto. The proposed evaluation of RoIs is based on their scientific importance as well as on the opportunities and conditions to observe them during the currently discussed mission profile. Highlights: We propose a selection of Regions of Interest (RoIs) on Ganymede and Callisto's surface. The RoIs represent surface features crucial to understand the evolution of these bodies. The list helps to fully exploit the potential of the JUICE mission. The list supports the observation planning and the synergy of the JUICE instruments.